Revisiting Public Debt Sustainability During the COVID-19 Pandemic in India - Kaur, Amanpreet; Kaur, Prabhjot (Indian Journal of Finance, 2023)
Purpose : The present study aimed to assess the impact of COVID-19 on public debt sustainability through a systematic literature review of prolific international studies and an evaluation of the trends of debt, deficit, and spending indicators over the past years. Methodology : Fourteen studies were systematically reviewed, and special attention was paid to the policy implications they suggested. The study also used data from secondary sources to unravel the trends of various fiscal indicators of the Indian economy for the period from 1982–1983 to 2020–2021. Furthermore, unit root and Johansen’s co-integration tests were employed to assess public debt sustainability. Findings : The review of studies revealed the significance of the policies aimed at reduction in debt servicing and expenditure, debt restructuring, maintenance of a rainy day fund, and market-financed public investment plan. The combined government finances depicted that the government’s fiscal position was unhealthy even before the pandemic, further aggravated by the latter. Practical Implications : The present research provided valuable insights for the policymakers and the government to manage the fiscal health of the economy through various policy measures, namely, judicious resource utilization, structural changes in revenue and expenditure policies, and a flexible fiscal framework. Originality : The present study provided a dual assessment of the impact of COVID-19 on public debt sustainability in India, given the scarce literature concerning the same.